Unmet Need for Modern Contraception among Urban and Ru-ral Women in Manipur- A Cross-Sectional Study - Dutta, Gitashree; Lyngdoh, Markordor; Akoijam, Brogen Singh (National Journal of Community Medicine, 2020)
Introduction: The concept of unmet need points to the gap between women's reproductive intentions and their contraceptive behaviour. Around 215 million women reproductive-aged women around the world have an unmet need for modern contraception. The present study is aimed to assess prevalence of the unmet need for family planning, its determinants, the reasons for the unmet need for family planning, and to suggest suitable measures to improve the utilization of contraceptive methods in urban and rural areas of Manipur. Methods: This Cross-Sectional study was done among 357 women of reproductive age group in in urban area of Athokpam in Thoubal district and rural area of Bishnupur district of Manipur from Oct-Nov 2017. A pre tested, structured questionnaire was used. Data were entered in IBM SPSS Statistics. Results: In the present study, 74.2% of the married women in urban area and 31.7% in rural area had unmet need for family planning. The unmet need observed in urban area was much higher than that of rural area. Conclusion: Women whose husbands approved the use of contraceptive methods were having less unmet needs for family planning than women whose husbands disapproved in urban area which was statistically significant.